Efektivitas Penggunaan Kurikulum Merdeka Belajar Sebagai Pengganti Kurikulum 2013 Dalam Dunia Pendidikan - Desi Suryati; Ummi Salamah; Mustafiyanti Mustafiyanti (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
In the world of education there is always something called change and renewal, whether in the teaching staff, the facilities used and so on, as well as the educational curriculum in indonesia, which continues to change. Such as the independent learning currriculum which was implemented as a replacement for the 2013 curriculum. Before it became the independent learning curriculum, an emergency curriculum was implemented due to the Covid-19 pandemic which hit the entire world. This independent curriculum also emerged because of circumstances that required changing the curriculum, and following develoments in today’s modern era. Therefore, this article discusses the effectiveness of using the independent learning curriculum as a substitute for the 2013 curriculum, using qualitative research methods. This researh by searching for data from books, journals, and scientific articles. The independent learning curriculum is a curriculum that prioritizes the interests and desires of student, and is based on te pancasila student profile which aims to ensure that students have characteristics of noble character.